Turismo Comunitario, Alternativa De Desarrollo Turístico Estudio De Caso: Estudio De Factibilidad Para La Implementación De Una Ruta De Turismo Comunitario De Las Comunidades Shuar Atahualpa, Shuar Nantip Y Waorani Ñoñeno Para El Cantón Francisco De Orellana, Provincia De Orellana - Velásquez, Carlos Renato Chávez; Guerra, Juan Hugo Rodríguez; Paredes, Oscar Iván Granizo; Vega, Jessyca Consuelo Chiriguayo; Mármol, Edison Eduardo Ruiz; Baquero, Juan Carlos Carrasco (European Scientific Journal, ESJ, 2017)
Ecuador is a diversified country with great potential for tourism. The diversity can be seen in the variety of natural and cultural attractions found in the four natural regions. Orellana province is an home of five different indigenous nationalities. Each of these nationalities has its own language, customs and traditions. The indigenous nationalities of Shuar, Kichwa, and Waorani are located in the Francisco de Orellana canton. This canton has important natural and cultural attractions, which makes the development of a community-based tourism project viable. The geographical location of the communities of Atahualpa, Nantip, and Ñoñeno makes it feasible to design a tourism route, which would help these communities to share their natural and cultural richness. These communities have had difficulties in structuring their resources in a technical way. Therefore, this study aims to integrate all the touristic attractions in order to advertise them to the public to achieve sustainability and increase their competitiveness in the market. In order to achieve this goal, a feasible study was carried out to implement a community-based tourism route. Based on the market study, it was determined that there is a high demand of national and international tourists who would like to visit a tourism route in this canton. Also, there is a high demand to visit the flora and fauna found in the Amazon region of Ecuador. Three touristic packages were developed, which bring together all the communities. As a result, it makes them more competitive in the area. In conclusion, the implementation of a community-based route that uses touristic packages, would allow the direct participation of the people in the communities, the sustainable use of natural and cultural resources, and a fair and equitable distribution of the income generated by the touristic activities.